Self-Esteem and Strategies to Increase The Student English Achievement - Skripsiani, Helly; Yukamana, Hanni; Tahrun, Tahrun (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
In this study, students in the state's senior high school number two in Musi Rawas' eleventh grade were asked about their self-esteem and strategies for improving their English proficiency. 64 students in the eleventh grade were selected as the sample for this study using cluster random selection. The correlational research design was used in this study. Data for the study was gathered via questionnaires and written records. They were examined using the Pearson Product Moment Correlation Coefficient and multiple regression analysis.The result showed that the sig. value of correlation between self-esteem and English achievement was 0.000 < 0.05, so H01 was rejected with 18.7% contribution of self-esteem. The sig. value of correlation between language learning strategies and English achievement was 0.000 < 0.05, so H02 was also rejected with 21.8% contribution of language learning strategies. The sig. change of correlation among self-esteem, language learning strategies, and English achievement was 0.000 < 0.05, automatically H03 was rejected with 24,3% contributions of self-esteem and language learning strategies.